Semi-superjunction IGBT with a relatively high-resistance p-top region for low on-state and turn-off losses. (October 2021) - Hu, Min; Huang, Mingmin; Li, Rui; Ma, Yao; Yang, Zhimei; Li, Yun; Gong, Min
Abstract: A semi-superjunction (semi-SJ) IGBT with a relatively high-resistance p-top region is proposed and studied by simulations. The p-top region is able to suppress the collection of holes by the p-pillar to enhance the carrier storage effect in the on-state, which helps to obtain excellent trade-off between turn-off loss ( E off ) and on-state voltage drop ( V CE(sat) ) . An n-drift layer is used to sustain a part of the applied voltage, so the thickness of the n/p-pillars can be decreased to reduce manufacturing cost and difficulties of superjunction (SJ). Compared to the conventional semi-SJ IGBT, the proposed semi-SJ IGBT has a nearly same E off and a 0.3–0.6 V lower V CE(sat) under pillar doping concentration N pillar = 4–8 × 10 15 cm −3 . Besides, it is interesting to find that the optimum design for minimum E off under the same V CE(sat) is not obtained in the full SJ case (i.e., the case without the n-drift layer), and minimum values of E off are very close under N pillar = 4–8 × 10 15 cm −3 . Highlights: Carrier storage effect enhanced by a relatively high-resistance p-top. With low losses and reduced fabrication complexity. Optimization for turn-off and on-state losses of superjunction IGBTs. Effect of pillar doping and thickness on turn-off loss. Analysis of turn-off process of superjunction IGBT.